Computerized Inventory of Publications - J. C.M. L'Arrivee (Journal of Applied Communications, 1978)
Computerized inventory control of publications became a necessity at the Canada Department of Agriculture because of the large number of titles on hand and the ever-increasing number of requests we receive.